Jurassic animals and algae in the flooring of Our Lady of Sorrows Church in Poznań - Antczak, Mateusz (Biological Letters, 2016)
The flooring of Our Lady of Sorrows Church in Poznań is made of Jurassic rocks from the Świętokrzyskie Mountains (also known as Holy Cross Mountains) and contain abundant marine invertebrate fossils: sponges, bivalves, brachiopods, various families of cephalopods, etc. Some of them can be identified to the genus level. The fossils make it possible to describe the environment and ecosystem of the Jurassic sea and biostratigraphy of the sediment. There are also some significant inorganic structures, which suggest post-diagenetic tectonic movements.